A brisk walk—Real-life travelling speed of lay responders in out-of-hospital cardiac arrest. (June 2020) - Jonsson, Martin; Berglund, Ellinor; Djärv, Therese; Nordberg, Per; Claesson, Andreas; Forsberg, Sune; Nord, Anette; Tan, Hanno L.; Ringh, Mattias
Abstract: Background: Defibrillation by public Automated External Defibrillators (AEDs) before EMS arrival is associated with high survival rates. Previous recommendSations suggest that an AED should be placed within a 1–1.5 min "brisk walk" from a cardiac arrest. Current guidelines hold no recommendation. The real-time it takes for a volunteer to retrieve an AED in a public setting has not been studied. Methods: Global Positioning System data and Geographical Information Systems methods were used to track the movement of mobile phone dispatched lay responders in two large Swedish areas. The distance and the travelling time were calculated from when the lay responder received the call, until they were within 25 m from the coordinate of the suspected OHCA sent by the dispatch centre. Results: During 7 months, a total of 2176 persons were included in the final analysis. The median travelling speed was 2.3 (IQR = 1.4–4.0) metres per second (m/s) among all cases with a response time of 6.2 min. The corresponding travelling distance was 956 m (IQR = 480–1661). In the most densely populated areas (>8000 inhabitants/km 2 ) the response time was 1.8 m/s compared to 3.1 in the least densely populated areas (0–1500 inhabitants/km 2 ). Conclusion: The median travelling speed of all lay responders dispatched to suspected OHCAs was 2.3 m/s. In densely populated areas the travelling speed was 1.8 m/s. This can be used as support in guidelines for planning placement of AEDs, in simulation studies, as well as in configuration of mobile-based dispatch systems.